Pesantren Kilat dalam Pembinaan Karakter Islami melalui Sinergi TPQ Desa Plosokerep - Dyah Ayu Sri Hartanti; Amrini Shofiyani; Fajar Mohammad Izzuddin; Ririn Fitriyani; Erna Dwi Widiya Ningrum; Abdun Nafi’ Mustajab; Tirto Sembiring; Bani Maftuh; M. Ahya Assyukri; Zuhroh Kamilatul; Indra Bayu Sadewo (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This community service program aimed to strengthen Islamic character education among children in Plosokerep village through a collaborative pesantren kilat involving nine TPQs. The main issue addressed was the limited variation and integration of learning materials in TPQs, which tended to focus only on reading iqra’ and memorizing short surahs. Using the Participatory Action Research (PAR) and Asset Based Community Development (ABCD) approaches, the program engaged 29 students as direct beneficiaries. Activities were conducted in TPQ Al-Madinah and integrated four main subjects: basic fiqh, akhlak, Arabic language, and Qur’an recitation (tahsin). Results show that more than 80% of participants improved their understanding and practice, particularly in Qur’an recitation and Islamic manners. A pesantren kilat module was produced as the main output, serving as a practical guide for TPQs to continue the program independently. The collaboration successfully fostered stronger networks among TPQs, increased social interaction, and contributed to the sustainable development of Islamic education in the community.